2017
DOI: 10.1149/2.0221709jss
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of CVD Grown Multi-Layer Graphene under Different Types of Precursors and Their Respective Flow Rate

Abstract: In this work, atmospheric pressure chemical vapor deposition (CVD) method was used to synthesize multi-layer graphene (MLG) on copper substrate. The MLG samples were grown under different type of liquid precursors, i.e. methanol, ethanol, and heptane, with different flow rate of hydrogen (H 2 ) (combination of both denoted as precursor flow rate). The transferred graphene film onto glass substrate have good coverage area as evident from AFM measurements, however, morphological differences were less notable amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It is clearly shown that the microsized MgCO 3 granules were orderly assembled by wafer-like nanosheets, unlike the general cubic structure with epitaxial growth along one crystalline direction [19]. The size of MgCO 3 granules was well controlled in the range of 5–10 μm, providing desirable platforms for the growth of graphene with microsized planar sheets [20]. Upon high-temperature decomposition, the MgCO 3 precursors were transformed to MgO templates with slightly decreased size, accompanied by the degradation of sheet thickness (Figure 1c,d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clearly shown that the microsized MgCO 3 granules were orderly assembled by wafer-like nanosheets, unlike the general cubic structure with epitaxial growth along one crystalline direction [19]. The size of MgCO 3 granules was well controlled in the range of 5–10 μm, providing desirable platforms for the growth of graphene with microsized planar sheets [20]. Upon high-temperature decomposition, the MgCO 3 precursors were transformed to MgO templates with slightly decreased size, accompanied by the degradation of sheet thickness (Figure 1c,d).…”
Section: Resultsmentioning
confidence: 99%
“…It was accompanied by the observation of D band located at 1330 cm −1 , pointing to the existence of structural defects of graphene. The 2D band (excited by a double-resonant Raman process) located at 2677 cm −1 was attributed to the double resonance effects of the D band, indicating the existence of few-layer graphene presented in G@MgO [20,29]. The presence of ordered and graphitized carbons attached to the MgO particles, instead of normal graphene oxide, probably contribute to the promotion of interfacial adhesion and TC [30].…”
Section: Resultsmentioning
confidence: 99%